USING POINT COUNTERPOINT METHOD TO IMPROVE SPEAKING ABILITY OF GERMAN LANGUAGE STUDENTS AT PATTIMURA UNIVERSITY - H. Serpara; K. Karuna; Maria M. Nikijuluw (SCIENCE NATURE, 2019)
This research is a classroom action research, which carried out to describe the development of students' speaking abilities as the effect of using the point counterpoint method. This research has been carried out in semester 5 (five) in academic year 2019/2020. The population of this study is the students of the German Language Study Program, while the selected sample is the 5th semester students in total 30 people. The procedure of this research was carried out in cycles, starting from planning, observation and reflection. Research instruments are test and non-test. The results of cycle 1 indicate that students have not yet reached a minimum score or passing grade, on average score of 58.93. The results of the second cycle test show that results increased, namely on average score of 72.5. Overall, the results of this study indicate that using a point counterpoint method can improve students' speaking abilities, especially in creative thinking and argumentation. Thus, using this method in teaching is useful to support the achievement of speaking competency at a B1-GER level.